Short communication: Length-frequency distribution, length-weight relationship and condition factor of two grey mullets from Lagos Lagoon - Olukolajo, Soyinka Olufemi; Sifau, Mutiu Oyekunle; Olude, Oluwagbenga Olanrewaju; Ashanabode, Osawe (Syiah Kuala University, 2023)
There is a growing interest in examining of economically important fish species with excellent mariculture potentials in lagoons of coastal states. Members of the family Mugilidae, which are permanent residents in Lagos Lagoon form a mainstay of fish protein source and are potential candidates for such investigations. Length-frequency distribution, length-weight relationship, condition factor and molecular characteristics of two grey mullets, Mugil cephalus and Liza falcipinniswere investigated in Lagos Lagoon. A total of 52 samples (26 specimens of each species) of the fish were collected from the Lagos Lagoon. The standard length ranged from 10.0 19.2 cm and 12.0 18.2 cm for M. cephalus and L. falcipinnis respectively, with corresponding weights of 13.90 105.00 g and 36.00-129.00 g respectively. The growth pattern of the species showed negative allometric, b = 0.32 and 0.65 respectively. The condition factors were 1.81 and 2.16 respectively and this meant both species were in good condition.